Exposure to JUUL use: cue reactivity effects in young adult current and former smokers. Issue 4 (23rd May 2020) - Vena, Ashley; Miloslavich, Krista; Howe, Meghan; Cao, Dingcai; King, Andrea C
Abstract : Background: Exposure to the use of first, second and third generations of electronic cigarettes (e-cigarettes) elicits the desire to vape and smoke among observers, as well as facilitates smoking behaviour. Given the rapid rise in the popularity of the pod mod JUUL, we examined whether observing the use of this device would elicit similar responses in smokers. Exploratory analyses were also conducted to determine whether JUUL can act as a smoking cue for former smokers. Methods: The sample consisted of 82 young adult participants (62 current smokers and 20 former smokers approximately 1 year smoke free). The study examined their response to observing use of bottled water (control cue) and JUUL (active cue) in a controlled laboratory paradigm. Both cues were delivered by a trained study confederate under the guise of a social interaction task, and participants completed mood and desire and urge surveys precue and postcue exposures. Results: In current smokers, exposure to the JUUL cue increased smoking urge and desire for a cigarette, mod/vape pen and JUUL, and two-thirds chose to smoke in the behavioural analogue task. In former smokers, the JUUL cue evoked modest and transient increases in desire for a cigarette and JUUL. Conclusions: The use of JUUL affects the user and elicits responses in observers; this study is the first to demonstrate that exposure to JUUL use may act as a smoking cue and exposure to JUUL use may affect tobacco control efforts.